LIST OF CHROMOSAN LUIS POTOSIHERIC FLARES FROM JULY 1ST TO SEPTEMBER 30TH 1957 - RIVERA TERRAZAS, LUIS; GONZALEZ C, GUILLERMINA (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1954)
On July 1st of 1957 Lyot filter observations at the Tonantzintla Observatory were initiated. The instrument is described here. During the first trimester of the International Geophysical Year the solar station at Tonantzintla carried out a constant patrol
BOL OBS TONAN TACUB
Keywords: LIST, CHROMOSPHERIC, FLARES, JULY, SEPTEMBER, 1957; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS